Improvements to the hybrid method applied to the design of plate-finned tube evaporators. Issue 1 (1st December 2022) - Starace, G; Macchitella, S; Colangelo, G
Abstract: The advantage of designing plate-finned tube evaporators applying the hybrid method is to combine low computational costs with the accurate results guaranteed by the use of predictive functions based on results of either numerical, or analytical, or experimental analysis. The high flexibility of the method makes it suitable for use as an effective design tool for evaporators in a wide range of operating conditions. This paper tells about improvements and refinements to the hybrid method algorithm performed to make it even more flexible and consistent with real heat exchangers performance prediction, depending on configuration changes. Part of the algorithm code has been changed in order to extend the application range of the model and several tests have been performed by varying the operating conditions such as the temperature difference between refrigerant and air at the inlet as well as the air relative humidity. The results show how the model is sensitive to the working conditions variations.